2012
DOI: 10.5604/17322693.991490
|View full text |Cite
|
Sign up to set email alerts
|

The influence of polymorphism of the MUC7 gene on the teeth and dental hygiene of students at a faculty of dentistry in Poland

Abstract: This study does not show a correlation between the MUC7 genotypes and caries and oral hygiene of students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
0
12
0
6
Order By: Relevance
“…About half of the selected studies analyzed children, 13,14,18,19,20 evaluating primary and permanent dentition, while the other half studied only adults. 12,15,21,22,23,24 Dental caries prevalence was evaluated according to the number of decayed, missing, and filled teeth. There has been no distinction between primary (dmft) and permanent (DMFT) dentition for indexing low and high risk of caries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About half of the selected studies analyzed children, 13,14,18,19,20 evaluating primary and permanent dentition, while the other half studied only adults. 12,15,21,22,23,24 Dental caries prevalence was evaluated according to the number of decayed, missing, and filled teeth. There has been no distinction between primary (dmft) and permanent (DMFT) dentition for indexing low and high risk of caries.…”
Section: Resultsmentioning
confidence: 99%
“…Two Polish studies have added to this knowledge by considering the role of their polymorphisms in caries experience, albeit with conflicting results. While Pol 12 has found an association between the MUC7 6/6 genotype and high dental caries experience (p=0.09), in a study with 158 young adults, Buczkowska-Radlinska et al 22 have reported that the distribution of the value of the DMFT index was similar to that of the control group. Vieira et al 10 suggested that these conflicting results might be related to study design issues such as population heterogeneity and statistical power, therefore not yet refuting the results of the original study.…”
Section: Records Identified Through Database Search (N= 424)mentioning
confidence: 97%
See 1 more Smart Citation
“…Mucins and proline-rich proteins take part in bacteria cell agglutination, including cariogenic bacteria [Darshana et al, 2014;Opal et al, 2015]. Researchers examined SNP in genes encoding salivary components -CA6 (for carbonic anhydrase 6), MUC 7 (for mucin), AQP (for aquaporin), and PRH1 (for prolinerich protein 1) [Peres et al, 2010;Yarat et al, 2011;Buczkowska-Radlińska et al, 2012;Koç Öztürk et al, 2012;Wang et al, 2012b;Li et al, 2015;Yildiz et al, 2016]. The relation of the CA6 gene with the buffer capacity of saliva was observed by Yildiz et al [2016] and Peres et al [2010].…”
Section: Discussionmentioning
confidence: 99%
“…Available studies in the literature have reported a number of the genes related with the following to be associated with lower or higher risk for caries experience: (1) enamel formation: Slayton et al [2005], Deeley et al [2008], Patir et al [2008], Kang et al [2011], Olszowski et al [2012], Shimizu et al [2012], Tannure et al [2012b], Wang et al [2012b], Ergöz et al [2014], Gasse et al [2013] and Jeremias et al [2013]; (2) immune response: Lehner et al [1981], de Vries et al [1985, Bergandi et al [2007], Altun et al [2008], Bagherian et al [2008], Azevedo et al [2010], Ozturk et al [2010], Brancher et al [2011], Pol [2011, Buczkowska-Radlińska et al [2012], Olszowski et al [2012], Valarini et al [2012], Fine et al [2013] and Krasone et al [2014]; (3) saliva: Zakhary et al [2007] and Wang et al [2012b], and (4) other genes: Tannure et al [2012a]. TAS1R2 gene rs35874116, Ile191Val variation has been found to be associated with lower habitual sugar intake [Eny et al, 2010].…”
mentioning
confidence: 99%